Brief Review and Mathematical Modelling of Air Cushioned Pressurized Paper Machine Headbox - Saini, Parvesh; Kumar, Rajesh (International Journal of Engineering and Technology, 2018)
Today, the requirement of high grade papers is increasing day by day. To cater the need of high quality papers, new high-speed paper machines are being developed constantly. The whole economy of a pulp and paper industry depends on the quality of paper produced, quality of paper depends on the efficient operation of the major part of paper industry â€“ paper machine. Paper machine is the heart of paper industry and has many subsystems. One of the important subsystem of paper machine is Headbox.Â Â To have the desired quality papers, efficient working of headbox is highly required. To have desired operation from headbox, its precise control is necessary. The precise modelling of headbox, leads to design of efficient controllers for its proper control to get the desired response. This paper presents the mathematical modelling of headbox along with a brief review of various research performed on headbox.Â Â